Removal of a foreign body by rigid bronchoscope after virtual reality-aided presurgical planning: A case report. (2022) - Torii, Atsushi; Saka, Hideo; Clapp, Tod; Eitel, Chad; Honjo, Chisato; Anzai, Masaki; Oki, Masahide
Abstract: Flexible bronchoscopy is becoming increasingly important for the removal of airway foreign bodies. However, in cases of risk of coughing during the procedure, rigid bronchoscopic intervention should be performed under general anesthesia. A 22-year-old man presented with history of several episodes of fever, for which he was administered antibiotics at a private clinic. In an annual chest X-ray and chest computed tomography examination, a foreign body, which appeared to be an orthodontic appliance, was discovered in the left main bronchus. It was deemed difficult to remove the foreign body using flexible bronchoscopy because of granulation tissue formation. Therefore, the patient was referred to our institution. We simulated the clinical situation using virtual reality, which indicated that the proximal and distal metallic parts of the appliance had grown into the bronchial mucosa. First, we inserted a rigid bronchoscope under general anesthesia and cut the granulation tissue using an insulation-tipped diathermic knife. Thereafter, we removed the appliance with grasping forceps under rigid bronchoscope guidance. In cases of risk of foreign body encroachment into the bronchial mucosa or granulation tissue development, rigid bronchoscopic intervention is effective. Furthermore, a VR-based intervention may be a useful option in such cases. Highlights: Virtual reality provides depth perception and spatial understanding for planning. A rigid bronchoscope can remove foreign bodies better than a flexible one. Cutting tracheal mucosa by an IT knife may be required in some cases.